The reactions of victims in bullying cases in Belgrade secondary schools - Adrijana (Norma, 2023)
The paper presents the research findings on the reactions of victims in bullying cases and the correlations between the reactions and the sex and age of the victims. The research was conducted in the 2020/2021 school year based on a survey of 1,506 students in grades II to IV at 19 secondary schools in the Belgrade District School Authority area. The main findings indicate that the most common reactions of victims are to avoid the bully or hit back, and that most victims do not seek protection. Significant similarities, but also differences, were found in relation to previous findings on reactions of victims in primary school in Serbia. There are two similarities: 1) avoiding the bully is at the top of the list of the most common reactions; and 2) in cases where victims seek protection, they seek it more often from adults than from peers and more often from teachers than from parents. On the other hand, two differences were found: 1) the order of the other reactions on the list differed, with suffering violence being more common among victims from primary school and hitting back being more common among victims from secondary schools; and 2) correlations were found between the reactions of victims and their sex and age in primary school, while they were not found in secondary schools. In relation to schools abroad, the findings are consistent with the fact that most victims do not seek protection, but there are differences in the case of victims seeking protection – in schools abroad they seek it more often from peers than from adults and more often from parents than from teachers, while the opposite is the case in Belgrade schools.